BRACING SEBAGAI TEKNOLOGI KONTROL SEISMIK PADA STRUKTUR RUMAH TRADISONAL SUMATRA - Mohammad Ihsan (Universitas Trisakti, 2018)
Sumatra Island is earthquake hazard area in Indonesia, because two continental plates generate subduction zone. In Sumatra there are many traditional house, function of traditional house is dwellings as well as community meeting halls because that have cultural and historical values. The ancestors have also learneda lot about natural events they have experienced, from this experience they can make earthquake resistant structures for large earthquake, the result is that the Traditional Houses can still stand firm. One of the seismic control technologies in Sumatran traditional house is bracing. In this paper the structure of Sumatran Traditional Houses modeled by numerical analysis and analyzed dynamically behavior from its structure. The analysis revealed the secrets of seismic bracing control in the structure of the Sumatran Traditional House.